The dark half - King, Stephen, 1947- (New York : Penguin, 1992)
With a bit of guilt, Thad retires George Stark, his pseudonym, only to have him appear as a killing machine that destroys everyone on the path that leads to the man who created him.
Booklist.
New York Times.
Wilson's Fiction.
Adult
Keywords: Murderers -- Fiction; Novelists -- Fiction; Horror fiction; Murderers -- Fiction; Novelists -- Fiction